Local wisdom as basic material for drafting local government regulations: A case study of Dayak forest fires in Kalimantan, Indonesia - Siombo, Marhaeni Ria (Linguistics and Culture Review, 2021)
The Dayak tribe is a native of Kalimantan's island, one of the large islands in Indonesia that has a large forest area. This study aims to determine the local wisdom of the Dayak tribe in managing forests to prevent forest fires to realize sustainable forest development. This research uses a descriptive method. The study was conducted on the Maanyan Dayak tribe in Muara Tewe, North Barito Regency, Central Kalimantan, Indonesia. Data was obtained employing observation, interviews. Focus group discussion and documentation. Data analysis using Triangulation Technique. Namely by collecting data, processing data, presenting data, and drawing conclusions. The study results show that the Dayak tribe has Local Wisdom, which provides guidelines for interacting with the forest. The Dayak tribe understands the relationship between humans and nature with a religious dimension that can be used to manage forests. This research is expected to be a material consideration for related parties to forest fire prevention by utilizing the local wisdom of the Dayak tribe.